S Stigma Dengan Kecemasan Masyarakat Tentang Covid-19 Di Ponorogo - Ririn Nasriati Nasriati; Dian Laila Purwaningroom; Rahma Tri Fany (LPPM Universitas Sari Mulia, 2022)
Background: A new virus named Covid-19, which was initially detected in the city of Wuhan in China and caused by Severe Acute Respiratory Syndrome Coronavirus 2, shocked the world at the end of 2019. (SARS CoV-2). Anxiety can also be caused by a new form of Covid-19, whose transmission spreads rapidly at the same time people experience anxiety. Stigma is a bad label obtained by inciting discrimination. Objective: To determine the relationship between stigma and public fear about Covid-19 in Mangkujayan Village, RT 02/RW 02, Ponorogo District, Ponorogo Regency. Method: A cross sectional, quantitative design was adopted in this study. The research population was 163 people in RT 02/RW 02, Mangkujayan District, Ponorogo Regency, and 62 respondents were randomly selected from this sample using a Simple Random Sampling approach. The questionnaire was used as an instrument (door to door). chi-square statistical test analysis. Result: The study showed 34 respondents (54.8 percent) experienced severe anxiety and 40 respondents (64.5 percent) experienced significant stigma. The results show a p value of 0.000 and an alpha of 0.05. In RT 02 RW 02 mangkujayan sub-district, ponorogo district, ponorogo district. Conclusion: There is a relationship between stigma and public anxiety with the close relationship achieved, namely CC = 0.611 is sufficient.